A mechanism of RGS14(414)-mediated recovery of an episodic memory loss: implication of GluR2 subunit of AMPA receptor - Masmudi-Martín, Mariam (Servicio de Publicaciones y Divulgación Científica, 2015)
Background and objectives: The ongoing quest for finding treatment against memory loss seen in aging and in many neurological and neurodegenerative diseases, so far has been unsuccessful and more effective and precise therapeutic strategies are needed. The study of memory enhancement seems to hold the potential for developing strategies to treat memory dysfunctions. In line to this, previously, we have shown that the delivery of RGS14(414) gene into V2 visual cortex of rodent’s brain enhanced object recognition memory, which is one of the most studied examples of episodic memory. This memory enhancement effect was of such extent that it converted short term memory of 45 minutes into long lasting long-term memory that could be traced even after many months. Therefore, we have tested first whether object recognition memory loss observed in normal aging and Alzheimer´s disease can be recuperated by the same RGS14(414) gene treatment. Further, we explored through various biological processes in brain to provide explanation of RGS14-mediated memory enhancement and recuperation of memory loss. -Results and discussion: In the present thesis work we found that: (i) RGS14(414) gene treatment not only led to full recovery of an episodic memory loss in rodent models of normal aging and Alzheimer´s disease, but also aided in maintenance of the elevated ORM levels for long time; (ii) GluR2, an AMPA receptor subunit, showed upregulated level as well as a dynamic participation in conversion of short-term ORM into long-term memory in RGS14 rats; (iii) Area V2, frontal cortex and perirhinal cortex, areas that participate in brain circuit responsible for ORM processing, are not dependent on each other in RGS14-mediated memory enhancement; This independency of these brain areas in memory enhancement suggests that they are individually adequate for treatment of memory loss, in spite of where the primary cause is localized in brain; (iiii) RGS14(414) gene treatment did not favor Hebbian synaptic plasticity, which included LTP, muscarinic receptor-dependent LTD, and depotentiation. Though underlying cause of this lack in plasticity is yet to be elucidated, we believe that a decrease in calcium influx through RGS14-mediated blockage of L-type calcium channel could trigger the impairments seen in Hebbian plasticity, and that RGS14-mediated ORM enhancement could be reliant on non-Hebbian forms of plasticity. -Conclusions: On one hand, the proteomic results showed that GluR2 subunit is a key in RGS14-mediated ORM enhancement. On the other hand, the behavioral results of memory loss recovery in rodent models and of memory enhancement in lesioned rats demonstrate that RGS14(414) gene therapy might be a viable strategy for the treatment of memory loss in patients.
Keywords: Sistema nervioso - Degeneración - Tesis doctorales; Alzheimer; RGS14; Memory-loss; GluR2; Aging